2021
DOI: 10.1007/s11103-021-01145-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of RST1 and RIPR proteins in plant RNA quality control systems

Abstract: To keep mRNA homeostasis, the RNA degradation, quality control and silencing systems should act in balance in plants. Degradation of normal mRNA starts with deadenylation, then deadenylated transcripts are degraded by the SKI-exosome 3′-5′ and/or XRN4 5′-3′ exonucleases. RNA quality control systems identify and decay different aberrant transcripts. RNA silencing degrades double-stranded transcripts and homologous mRNAs. It also targets aberrant and silencing prone transcripts. The SKI-exosome is essential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…In line with recently characterized network of interactions between the exosome and SKIc in plants (Lange et al, 2019), silencing of RST1 or RIPR, encoding factors linking both multimeric assemblies inhibited degradation of 5 0 cleavage fragments generated during NGD, as well as nonstop reporters in N. benthamiana (Auth et al, 2021), demonstrating that RST1 and RIPR play pivotal roles in controlling efficiency of these two pathways, by coordinating functions of the plant exosome and its cytoplasmic adapter. Another class of events which require cooperation between the exosome, RST1, RIPR, and SKIc in plants is the degradation of 5 0 cleavage fragments induced by minimum uORF (AUG-stop) present in the 5 0 -UTR of a subset of plant genes (Auth et al, 2021).…”
Section: Nsd and Ngd In Higher Eukaryotessupporting
confidence: 76%
See 1 more Smart Citation
“…In line with recently characterized network of interactions between the exosome and SKIc in plants (Lange et al, 2019), silencing of RST1 or RIPR, encoding factors linking both multimeric assemblies inhibited degradation of 5 0 cleavage fragments generated during NGD, as well as nonstop reporters in N. benthamiana (Auth et al, 2021), demonstrating that RST1 and RIPR play pivotal roles in controlling efficiency of these two pathways, by coordinating functions of the plant exosome and its cytoplasmic adapter. Another class of events which require cooperation between the exosome, RST1, RIPR, and SKIc in plants is the degradation of 5 0 cleavage fragments induced by minimum uORF (AUG-stop) present in the 5 0 -UTR of a subset of plant genes (Auth et al, 2021).…”
Section: Nsd and Ngd In Higher Eukaryotessupporting
confidence: 76%
“…Silencing of RST1 or RIPR encoding SKIc‐exosome bridging factors resulted in the accumulation of vsiRISC‐ or miRISC‐generated 5′ cleavage products (Auth et al, 2021). Furthermore, RST1 mutations suppressed transgene silencing, and RST1 restricted production of transgene‐derived siRNAs and ct/rqc‐siRNAs originating from endogenous PTGS‐prone mRNAs, together with RIPR and the exosome (Lange et al, 2019).…”
Section: Skic Functions In Rna Decay and Surveillancementioning
confidence: 99%
“…In addition, the rst1 mutants have an abnormal leaf shape, late inflorescence emergence, and stunted embryo development, which results in nonviable seeds ( Chen et al, 2005 ). In addition, RST1 connects the Ski complex to the RNA exosome ( Lange et al, 2019 ; Li et al, 2019 ; Auth et al, 2021 ). Multiple virescent leaf mutants are caused by abnormalities in the basic functions of the chloroplast, including RNA metabolism ( Kusumi et al, 2004 ; Sugimoto et al, 2007 ; Zhang et al, 2018b ; Mao et al, 2019 ) and protein metabolism ( Koussevitzky et al, 2007 ; Dong et al, 2013 ; Xing et al, 2014 ; Song et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…RST1 plays a role in plant defense ( Mang et al, 2009 ) and controls the dynamic balance of plant membrane proteins ( Zhao et al, 2019 ). Recent research on RST1 has made breakthroughs ( Lange et al, 2019 ; Li et al, 2019 ; Auth et al, 2021 ). For example, the formation of higher-order complexes by RNA exosomes and RST1 has been identified that catalyze RNA maturation and degradation ( Lange and Gagliardi, 2022 ; Lee and Suh, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reverse IP experiments using RST1 and RIPR as baits confirmed their association with the exosome complex and indicated that they may link Exo9 with the Ski complex ( Lange et al, 2019 ). A recent study showed that RST1 and RIPR were required for the degradation of NGD and NSD model substrates that were transiently expressed in Nicotiana benthamiana leaves ( Auth et al, 2021 ). Yet, the molecular functions of RST1 and RIPR remain to be identified.…”
Section: Cytoplasmic Exosomesmentioning
confidence: 99%